Associations of dietary diversity score, obesity, and high-sensitivity C-reactive protein with HbA1c - Irmayanti, Irmayanti; Farmawati, Arta; Purba, Martalena Br (UI Scholars Hub, 2019)
Background: Associations of dietary diversity score (DDS), obesity and high-sensitivity C-reactive protein (hs-CRP) with glucose metabolism have been reported. Furthermore, DDS may not be associated with healthy weight. However, studies on these topics are limited in general Indonesia population. Methods: A total of 3,825 Indonesia Family Life Survey 2014/2015 participants aged 20-59 years old were included in this study. DDS was measured qualitatively in five food groups: carbohydrates, proteins, dairy products, vegetables, and fruits. Obesity was defined by Body Mass Index (BMI) classification for Indonesians. Blood analyses were performed in dried blood spot specimens. hs-CRP were analyzed using enzyme-linked immunosorbent assay and HbA1c was analyzed using Bio-Rad D10. Results: High DDS group had higher HbA1c than low DDS group (p = 0.030). Furthermore, medium and high DDS group had higher BMI than low DDS group (p = 0.003 and < 0.001). Obese group had higher HbA1c than nonobese group (p < 0.001). hs-CRP was correlated with HbA1c (r = 0.1194; p < 0.001). Multivariate analysis showed that DDS, obesity and hs-CRP were associated with HbA1c (p = 0.030, p < 0.001 and < 0.001). Conclusions: Present study confirmed that obesity and hs-CRP are associated with HbA1c. DDS is positively associated with HbA1c and BMI. Promoting dietary diversity requires careful consideration. Moreover, further studies are warranted.